Kewenangan Fungsi Legislasi pada Eksekutif dalam Pembentukan Undang-Undang Ibu Kota Negara - Angelika, Bunga; Luluardi, Yunas Derta (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to reveal the Authority of the Legislative Function of the Executive in the formation of the National Capital Law. After the Amendment to the 1945 Constitution, it resulted in changes in the design of the Indonesian state administration, one of which was the change in the function of state institutions. Regarding the formation of laws, the amendment to Article 5 Paragraph (1) and Article 20 of the 1945 Constitution has presented its own dynamics in the legislative function. The research method used is normative juridical which discusses doctrine or legal principles to create new arguments, theories or concepts to solve problems, with a statutory, comparative and conceptual approach that uses library materials as the main legal material to analyze the legislative function of the executive in the formation of the National Capital Law. The results of this study indicate that after the amendment to the 1945 Constitution, the institutions that can submit draft laws are not only the DPR and the President but the DPD can also submit draft laws. The formation of the National Capital Law was formed by the Executive (President). The legal consequences of the ratification of the National Capital Law gave birth to a law and changed a legal situation. The birth of the law is proven by the existence of a derivative form of the National Capital Law.